Discovery of asphalt seeps in the deep Southwest Atlantic off Brazil. (December 2017) - Fujikura, Katsunori; Yamanaka, Toshiro; Sumida, Paulo Y.G.; Bernardino, Angelo F.; Pereira, Olivia S.; Kanehara, Toshiyuki; Nagano, Yuriko; Nakayama, Cristina R.; Nobrega, Marcos; Pellizari, Vivian H.; Shigeno, Shuichi; Yoshida, Takao; et al.
Abstract: The discovery and description of cold seeps with deep-sea chemosynthetic communities in the Southwest Atlantic Ocean are still incomplete, despite the large proven oil and gas reserves off the coast of Brazil. In the southeastern Brazilian continental margin, where over 71% of the country's oil and gas production takes place, there are previous geological and qualitative biological evidence of seep biota associated with pockmarks on the upper slope of the Santos Basin. In order to further study seep ecosystems on the Brazilian margin, a deep-sea investigation named Iatá-Piúna cruise was conducted using the human-occupied vehicle Shinkai 6500 off Brazil's southeast continental margin. Asphalt seeps were discovered on the seafloor of the North São Paulo Plateau from depths of 2652–2752 m, representing only the third discovery of this type of seep worldwide, following those in the Gulf of Mexico and off Angola. Video and isotopic analyses indicated a number of megabenthic animals in the asphalt seeps in the North São Paulo Plateau and revealed typical deep-sea heterotrophic and photosynthesis-based fauna occupying hard substrates provided by the asphalt seep. There was no evidence of chemosynthesis-based megabenthic fauna such as vesicomyid clams, Bathymodiolus mussels, and siboglinid tube worms, or any sediment bacterial mats, gas seepage, and carbonate rock in/around the seeps. The benthic fauna was composed mainly of sponges (ca. 15 species), such as the hexactinellids Caulophacus sp., Poliopogon amadou, Saccocalyx pedunculatus, Farrea occa and cf. Chonelasma choanoides ; besides typical deep-sea isidid octocorals, brisingid starfishes and galatheid crabs. The δ 13 C values of poriferan sponges suggested a heterotrophic and pelagic nutrition. Geochemical analyses of asphalt revealed a heavy biodegradation of hydrocarbon molecules, supported by the depletion of light n -alkanes and other labile compounds. This advanced asphalt biodegradation is the likely reason for the absence of chemosynthetic communities at these seep sites.